Hubungan Antara Praktik Higiene Penjamah Dengan Keberadaan Coliform Pada Cincau Hitam Yang Dijual Di Lingkungan Kampus Universitas Muhammadiyah Surakarta - Prasetyo, Arif Hari; , Pramudya Kurnia, STP, M.Agr; , Fitriana Mustikaningrum, S.Gz, M.Sc (2016)
Introduction : Food contamination is the presence of dangerous material or organism in food unintentionally. Coliform is a kind of bacteria which often becomes the cause of contamination in food. Bacteria coliform can be used as an indicator of water contamination or food contamination because its presence is an indication of the occurence of contamination by the pathogenic bacteria. Based on the way of selling, the vendors have a bigger risk of 4.91 times to experience contamination than the culinary service providers. Cincau (grass jelly) is a kind of drink which susceptible to contamination because most of the material originated from the water. Sanitation of food snacks in Indonesia has not been paid attention well, therefore contamination by many kinds of microorganism often occurs. Objective : The purpose of the research was to determine the correlation between practice with the presence of hygiene handlers coliform cincau hitam in the campus University of Muhammadiyah Surakarta. Research Methodes : The research used cross-sectional design. Total sample 5 subjects were selected in total sampling. Data handlers practices higene obtained through direct observation using observation questionnaire data were obtained using the presence of coliform MPN coliform. Data were analyzed with Fisher Correlation test. Result : As many as 80% of the subjects in the category higienenya practices unfavorable. All samples studied contain coliform with the number reaching 1100 MPN/ml. The result of correlation test between hygiene practices handlers and presence of coliform (ρ=0,200). Conclusion : There is no correlation between hygiene handlers to the presence of coliform on black grass jelly sold in the campus of University of Muhammadiyah Surakarta. Suggestion : Needs to be socialization to black grass jelly sellers on how to touch the food was good and right in accordance with the guidelines Practice good hygiene and correct according to Kepmenkes 942 / Menkes / SK / VII / 2003.